Automated Video Surveillance System With Sms Alert (International Journal of Engineering and Computer Science, 2017)
in this paper presents a technique for motion detection that incorporates several innovative mechanisms. For example, our proposed technique stores, for each pixel, a set of values taken in the past at the same location or in the neighborhood. It then compares this set to the current pixel value in order to determine whether that pixel belongs to the background, and adapts the model by choosing randomly which values to substitute from the background model. This approach differs from those based upon the classical belief that the oldest values should be replaced first. In this future enhancement of paper is remotely we are checking and providing the security to our system. So whenever user getting SMS from server system and the background image is updated whenever the system is detecting a motion.